Performance of the revised Atlanta and determinant-based classifications for severity in acute pancreatitis. Issue 4 (25th January 2016) - Bansal, S S; Hodson, J; Sutcliffe, R S; Marudanayagam, R; Muiesan, P; Mirza, D F; Isaac, J; Roberts, K J
Abstract: Background: Severity classification systems aim to stratify patients with acute pancreatitis reliably into coherent risk groups. Recently, the Atlanta 1992 classification has been revised (Atlanta 2012) and a novel determinant-based classification (DBC) system developed. This study assessed the ability of the three systems to stratify disease severity among patients with acute pancreatitis. Methods: This was an observational cohort study of patients with acute pancreatitis identified from an institutional database. Cohort characteristics, investigations, interventions and outcomes were identified. Systems were compared using receiver operating characteristic (ROC) analysis and Spearman's correlation coefficients. Results: The in-hospital mortality rate was 6·6 per cent (15 of 228 patients). All of the outcomes considered correlated significantly with the three systems, with the exception of the need for surgery in Atlanta 1992. Atlanta 2012 and the DBC had higher area under the curve (AUC) values than Atlanta 1992 for all outcomes. The revised Atlanta and DBC systems both performed similarly with regard to ICU admission (AUC 0·927 and 0·917 respectively; both P < 0·001), need for percutaneous drainage (AUC 0·879 and 0·891; both P < 0·001), need for surgery (AUC 0·827 and 0·845; P = 0·006 and P = 0·004 respectively) and in-hospital mortality (0·955 and 0·931; both P < 0·001). However, the critical category in the DBC system identified patients with the most severe disease; seven of eight patients in this group died in hospital, compared with 15 of 34 with severe pancreatitis according to Atlanta 2012. Conclusion: The Atlanta 2012 and DBC perform equally well for classification of disease severity in acute pancreatitis. The addition of a critical category in the DBC identifies patients with the most severe disease. Abstract : Both systems define severe disease